Effect of Reflex Zone Therapy on Labor Pain Among Antenatal Mothers: A Descriptive Study - Linju T.K. (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Background: Pregnancy and childbirth are considered the completion of a woman’s life. Pregnancy is a period of carrying a fetus in the womb of a mother. During the period of 9 months and 7 days, a pregnant woman may undergo several physiological and anatomical changes. Hence pregnancy is a special time of life in a woman’s life. Labor pain is an excruciating pain that lasts for several minutes to hours according to the contraction of the uterus. The process of labor has three stages. Aim: The objective of the research was to assess the impact of reflex zone therapy on the pain experienced during labor among expectant mothers admitted to labor rooms in specified hospitals within Kannur district. Materials and Methods: A quasi-experimental methodology was employed in the study. The sample consisted of 60 primigravida mothers admitted in the labor room with cervical dilatation of 2 to 6 cm. The participants were selected using a convenience sampling method. Results: The collected information was investigated by using descriptive and inferential statistics. The findings of the study exposed that there is a significant variation in the level of labor pain among antenatal mothers in the experimental group after reflex zone therapy (p < 0.05). So H1 is accepted. The findings also revealed that there is an association between level of labor pain and educational status (p 0.05). So H2 is partially substantiated. Conclusion: The findings of the study revealed that reflex zone therapy can reduce labor pain. Thus, it can be used as routine care in the labor room to reduce labor pain.
Keywords: Health; Nursing; Pregnancy; antenatal mothers; gynecology; labor pain; reflex zone therapy